Biotechnological exploitation of agricultural products III - Bustos Vázquez, Guadalupe (Libros UAT, 2018)
Biotechnology allows the bioconcentration of agroindustrial resudues in products of commercial interest through the use of microorganisms. In addition to the economic interest involved in the production of higher value-added products (enzymes, unicellular protein, pigments, antibiotics, etc.), the use of agro-industrial by-products has an impact on the preservation of the environment when considering the development of oriental technologies towards a sustainable transformation of natural resources. The search for low cost raw materials and easy acquisition to be used as fermentable substrates (carbon or nitrogen sources), constitutes one of the most interesting challenges of current biotechnology. For this reason, research aimed at finding alternative farming methods that are economically competitive is of particular importance. In this sense, there are several byproducts of agro-industry that could be used as non-conventional substrates to obtain products of economic interest such as food additives.